Optimizing the Creative Industry Through the Development of the Triple Helix Model - Ratna Wijayanti Daniar Paramita; Noviansyah Rizal; Riza Bahtiar Sulistyan; Muchamad Taufiq; Muhammad Dimyati (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this research is to optimize the creative industry through the development of a triple helix model that connects universities, industry, and government. Design/methodology/approach: The method used is an ethnographic approach starting from the collection of literature sources and supported by field data. Findings: The results showed that batik entrepreneurs in Lumajang district, apart from preserving culture, were also used to improve the economy of the surrounding community. The batik culture is in the form of regional motifs such as the batik motif of the great banana, sand, and semeru mountain which are applied to the cloth with the batik process which will later be used as uniforms for the Lumajang Regency Government. Increasing the capacity of batik craftsmen also needs improvement through training activities. Research limitations/implications: This research is limited to bamboo craftsmen in Papring Banyuwangi. Practical implications: This research can be used as input for stakeholders to be used as a reference in optimizing the creative industry. Originality/value: This paper is original Paper type: Research paper